A comparative study on biologically and chemically synthesized silver nanoparticles induced Heat Shock Proteins on fresh water fish Oreochromis niloticus. (November 2015) - Girilal, M.; Krishnakumar, V.; Poornima, Paramasivan; Mohammed Fayaz, A.; Kalaichelvan, P.T.
Graphical abstract: Highlights: IC50 values of biologically and chemically synthesized nanoparticles were compared. Fishes were exposed to different concentrations of silver nanoparticles. Comparative stress physiology analysis by immunohistochemistry was carried out. Heat Shock Protein (HSP70) secretion analysed in the fresh water fish O. niloticus . Results compare the cytotoxic effects of silver nanoparticles in different tissues. Abstract: The wide applicability of silver nanoparticles in medicine and pharmaceutical industries leads to its over exploitation and thus contaminating our environment. Majority of these nanoscale dimension particles finally accumulates in fresh water and marine ecosystem. As the nanoparticles behave entirely different from its corresponding bulk material, a better understanding of their environmental impacts in aquatic ecosystems is inevitable. The study was focused on a comparative stress physiology analysis of chemically synthesized silver nanoparticles and biogenic silver nanoparticles. Half maximal inhibitory concentration of biologically synthesized and chemically synthesized nanoparticles was found out (30 μg/mL and 20 μg/mL respectively). The Heat Shock Protein (HSP70) secretion was analysed in the fresh water fish Oreochromis niloticus after exposing to different concentrations of biologically and chemically synthesized silver nanoparticles along with the silver in its ionic form. The intense immune-histochemical staining of fish tissues (muscle, kidney and liver) analyzed proportionately reflected the stress created. The colour intensity was directly proportional to the stress created or the stress protein released. High level of HSP70 expression was observed in all of the fish tissues exposed to silver ions and chemically synthesized silver nanoparticles, when compared to that of biologically synthesized. The results revealed the significance of comparatively safe and less toxic biogenic nanoparticles compared to the chemically synthesized.